Handbook of Social Capital and Regional Development 2016
DOI: 10.4337/9781783476831.00011
|View full text |Cite
|
Sign up to set email alerts
|

Dealmakers in place: social capital connections in regional entrepreneurial economies

Abstract: in place: social capital connections in regional entrepreneurial economies, Regional Studies. This paper examines the internal anatomy of regional social capital and develops a role for dealmakers -individuals who provide active regional stewardship. An empirical analysis of twelve US regions finds great variation in the presence of dealmakers. The strong local presence of dealmakers is correlated with high start-up rates. The empirical results suggest that the local presence of dealmakers is more important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Cultures that create a high social status for entrepreneurship and which normalise intensive networking help actors understand the value of participating in an entrepreneurial ecosystem. Recent work on dealmakers within entrepreneurial communities suggests that associating entrepreneurial support with civic pride is a powerful motivator for highly networked individuals to actively contribute to their ecosystem (Feldman and Zoller, 2012). As Feldman (Feldman, 2014 p. 4) argues: "a spirit of authenticity, engagement, and common purpose if the particular feature that differentiates successful [entrepreneurial] places."…”
Section: Governing Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…Cultures that create a high social status for entrepreneurship and which normalise intensive networking help actors understand the value of participating in an entrepreneurial ecosystem. Recent work on dealmakers within entrepreneurial communities suggests that associating entrepreneurial support with civic pride is a powerful motivator for highly networked individuals to actively contribute to their ecosystem (Feldman and Zoller, 2012). As Feldman (Feldman, 2014 p. 4) argues: "a spirit of authenticity, engagement, and common purpose if the particular feature that differentiates successful [entrepreneurial] places."…”
Section: Governing Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…As well as being a serial entrepreneur, as a key dealmaker, he invested in more than 80 other firms in Ottawa . Feldman and Zoller (2012) show that firm births are closely associated with the prevalence of dealmakers, especially well-connected dealmakers like Matthews. Research across 12 US regions found dealmakers who use their connections to 'make things happen' exert a strong positive influence on recipients firms' employment and sales, but have no influence on the likelihood of them getting acquired (Kemeny et al, 2015, p2).…”
Section: The Role Of 'Dealmakers'mentioning
confidence: 99%
“…Some authors have used 'dealmakers' as a proxy for the evidence of dynamism within ecosystems (Napier and Hansen, 2011;Feldman and Zoller, 2012). However, this kind of single indicator analysis is susceptible to misinterpretation and could over-emphasis a single constituent actor within EEs.…”
Section: Measuring Entrepreneurial Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A company's social capital is a measure of its relationships with its ecosystem [1,2]. Social capital correlates with entrepreneurial success when the startup is in an innovation cluster [3][4][5][6], and has been found to be more indicative of entrepreneurial success than intellectual property [7].…”
Section: Introduction: Social Capital and Critical Mass In Business Imentioning
confidence: 99%